Older Adults with Alzheimer’s Disease, Comorbid Arthritis and Prescription of Psychotropic Medications - Judith E Balfour; Norm O’Rourke (Pain Research and Management)
OBJECTIVES: It is assumed that analgesia is underutilized among those with Alzheimer disease and that these patients may be inappropriately prescribed neuroleptics and benzodiazepines. The current study examines this assertion.